A Coupled Line Impedance Transformer for High Termination Impedance with a Bandpass Filtering Response - Phirun Kim; Yongchae Jeong (Journal of the Korean Institute of Electromagnetic Engineering and Science, 2018)
In this study, a short-ended coupled line with a short-circuit stub transmission line bandpass filtering impedance transformer is presented. The general designed equations are derived on the basis of circuit theory. The design curves are provided to examine the characteristic of the proposed impedance transformer. The proposed circuit is suitable for high termination impedance. To validate the design formulas, a 400–50 Ω impedance transformer is designed and fabricated at the operating center frequency (f0) of 2.6 GHz. The measured results show a good agreement with the simulation. The measured insertion and return losses are 0.6 dB and 22.5 dB at f0, respectively. The measured return loss is higher than 20 dB within the passband frequency of 2.51–2.7 GHz. Moreover, the stopband attenuation is higher than 25 dB from DC to 1.64 GHz of the lower stopband and from 3.12 GHz to 6.4 GHz of the higher stopband.